Combustion of extracted Rape Seeds - Kolomaznikova, Helena; Ondracek, Jaroslav; Skala, Zdenek (agricultural engineering.eu, 1998)
Larger utilization of rape oil for technical purposes increases the necessity to use the by-products from the oil pressing process. This by-product is extracte drape seed meal , which has a residual oil content of 2–3 %. Besides the utilization as foodstuff, it is necessary to find other ways of using of which one is for energy utilization. We solved the combustion of extracted rape seed meal. Essential fuel characteristics were found out and practical burning tests for emission determination releasing in their combustion were carried out. Gross calorific value of a standard sample (water content of 10 %, oil content of 2,6 %) is18,6 MJ/kg and calculated net calorificvalue is 17,1 MJ/kg. The combustion of extracted rape seeds in a boiler ARK 1000 with a fluid pre-combustor showed that it was possible to burn extracted seeds without any problems. All emission Iimits formulated by law were fulfilled, except the CO-contents in flue-gas caused by the bad technical state of the boiler.